IMPLEMENTATION OF THE “ESG” CONCEPT IN JOINT-STOCK COMPANIES - Ibragimova Saodat Abdumuminovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2026)
The article examines the principles of ESG (environmental, social and governance aspects) in corporate governance and their impact on the organization’s performance, analyzes the factors that contribute to the sustainable development of companies, strengthening their social responsibility and environmental sustainability, As well as increasing corporate value through the implementation of ESG standards, scientifically based proposals and recommendations were also developed that assess the impact of ESG principles on economic performance, investment attractiveness and corporate reputation.